2021
DOI: 10.1097/fjc.0000000000001183
|View full text |Cite
|
Sign up to set email alerts
|

Association of SGLT2 Inhibitors With Risk of Atrial Fibrillation and Stroke in Patients With and Without Type 2 Diabetes: A Systemic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…We observed that SGLT2i use was associated with a lower risk of incident AF compared with GLP-1RA use, consistent with the existing literature [ 31 ]. SGLT2i use was shown to be associated with lower risk of incident AF compared with placebo [ 7 ]. In contrast, results from both meta-analyses of randomized controlled trials and observational studies showed no significant benefits with GLP-1RA use on reducing incident AF compared with placebo [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that SGLT2i use was associated with a lower risk of incident AF compared with GLP-1RA use, consistent with the existing literature [ 31 ]. SGLT2i use was shown to be associated with lower risk of incident AF compared with placebo [ 7 ]. In contrast, results from both meta-analyses of randomized controlled trials and observational studies showed no significant benefits with GLP-1RA use on reducing incident AF compared with placebo [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding GLP-1RA, exploratory analysis of REWIND trial suggested that dulaglutide was associated with lower risk of ischemic stroke but neutral on hemorrhagic stroke compared with placebo [ 6 ]. Furthermore, SGLT2i was shown to be associated with lower risk of incident atrial fibrillation (AF) [ 7 ], but not for GLP-1RA [ 8 ]. Whether this may imply differential benefits on the risk of cardioembolic stroke between SGLT2i and GLP1-RA users remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 A meta-analysis of existing RCTs suggests that SGLT2 inhibitors may indeed be associated with a lower risk of incident AF (odds ratio 0.82 [95% CI 0.72-0.93]; P = 0.002), consistent with our study. 23 While the potential antiarrhythmic mechanisms of SGLT2 inhibitors 11,24,25 should theoretically result in a reduction of both supraventricular and ventricular arrhythmias, the bulk of the evidence from RCTs suggests that SGLT2 inhibitors do not affect ventricular arrhythmias or sudden cardiac death. 26,27 In one meta-analysis, however, a significantly lower risk of VT was observed (relative risk 0.73 [95% CI 0.53-0.99]).…”
Section: Discussionmentioning
confidence: 99%
“…A recent metanalysis by Zheng et al included 20 randomized trials involving 63,604 patients, most of them with DM. The primary analysis evaluated the incidence of AF and stroke [ 78 ]. The SGLT2 inhibitors evaluated were dapagliflozin (seven studies, 28,834 patients), empagliflozin (five studies, 9082 patients), canagliflozin (seven studies, 17,440 patients), and ertugliflozin (one study, 8246 patients).…”
Section: Effect Of Sglt2 Inhibition In Atrial Fibrillation: Clinical ...mentioning
confidence: 99%